Manajemen Lingkungan Fisik Sekolah Di Sekolah Dasar Negeri 6 Kota Manna - Susmiarti, Heti; Putri Kartiwi, Asti; Somantri , Manap (Manajer Pendididikan, 2024)
The purpose of this study was to evaluate the physical environment of schools in elementary school number six Manna city, which included: Planning the development of the school's physical environment, promoting the development of the school's physical environment, implementing the development of the school's physical environment, evaluating the school's physical environment development program. Specific research problems, namely: How to plan the development of the school's physical environment ?, How to socialize the development of the school's physical environment, How to carry out the development of the school's physical environment?. The study is an evaluative study, to evaluate the management of the school environment. Subjects are principals, teachers, curriculum sections, students, secondary subjects are people who are in the same environment. Data collection techniques used were observation, interviews and documentation. The results of the study are: Planning the physical environment at school has not been made formally and planning documentation has not been found. Program evaluation, Factors that inhibit the implementation of the school environment development program are lack of funds. The socialization of the school environment program, although there is no planning of the school environment program, it still exists. The implementation of the school environment program was carried out not by a team. Evaluation of the school environment development program looks at the existing conditions. Suggestions, planning the physical environment at school must be formally developed and documented. Programs need to be socialized. The implementation of the school environment program is carried out according to the plan to form a team. Program evaluation needs to be done with the aim to find out the success of the program in school environment management.